TINGKAT ADOPSI TEKNOLOGI USAHATANI PADI LAHAN SAWAH DI JAWA TIMUR : Suatu Kajian Model Pengembangan “Cooperative Farming” - Wahyunindyawati ;; F. Kasijadi; Heriyanto ; (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2003)
The study aimed at assessing factors affecting farmers to adopt technology of lowland rice farmingsystem using cooperative farming model. The study was conducted in Jember district during the wet season of2000/2001. Total samples were 105 farmers and data collection was done through a farm record keeping method.Data were analyzed using logit function. The results showed that factors affecting farmers’ adoption of culturalpractices were plant spacing within a legowo parallel system, choice of improved variety of Way Apu Buru,quantity of seed, and balanced fertilizer in the specific location. Factors affecting adoption of legowo parallelsystem and choice of the Way Apu Buru variety were costs of inputs, total labor, farming experiences, andprofitability. The factor of land area affected only plant spacing of legowo parallel system. Adoption of seedapplication was affected by total labor, land area, and educational background of the farmers. Balanced fertilizerapplication in the specific location was affected by costs of inputs and profitability. To encourage farmers toadopt new technology of rice farming system in the cooperative farming model, it requires the governmentprograms to improve farmers’ skills and knowledges through extension and capital credit.Key words : technology adoption, rice field, cooperative farming. Tujuan penelitian adalah untuk mengkaji faktor-faktor yang mempengaruhi tingkat adopsi petaniterhadap teknologi sistem usahatani padi di lahan sawah dalam model cooperative farming. Penelitiandilaksanakan di Kabupaten Jember pada musim hujan 2000/2001. Total petani contoh sebanyak 105 orang, danmetode pencatatan usahatani farm record keeping method digunakan dalam pengumpulan data. Analisa datamenggunakan model fungsi logit. Hasil penelitian menunjukkan keragaman faktor-faktor yang mempengaruhitingkat adopsi petani terhadap beberapa teknologi budidaya, antara lain : jarak tanam sistem jajar legowo;pemilihan varietas unggul padi Way Apu Buru; jumlah benih yang digunakan; dan penggunaan pupukberimbang spesifik lokasi. Faktor yang mempengaruhi adopsi jarak tanam sistem jajar legowo dan pemilihanvarietas Way Apo Buru adalah biaya sarana produksi, jumlah tenaga kerja, pengalaman usahatani dan tingkatkeuntungan. Faktor luas lahan, hanya mempengaruhi adopsi jarak tanam sistem jajar legowo. Adopsipenggunaan benih dipengaruhi oleh jumlah tenaga kerja, luas lahan dan tingkat pendidikan petani. Sedangkanpenggunaan pupuk berimbang spesifik lokasi dipengaruhi oleh biaya sarana produksi dan tingkat keuntungan.Dalam upaya peningkatan adopsi petani terhadap teknologi usahatani padi dalam model kooperatif usahatanimasih diperlukan dukungan program peningkatan pengetahuan dan keterampilan petani melalui penyuluhan danbantuan permodalan.Kata kunci : adopsi teknologi, padi sawah, usaha kooperatif